Dielectric Relaxation Spectroscopy of Liquid Crystal in Nematogenic Mesophase. (11th February 2016) - Tripathi, Pankaj Kumar; Manohar, Rajiv; Singh, Shri
ABSTRACT : In the present study, we report the dielectric behavior of a high temperature nematic liquid crystal (NLC) in both the planar as well as homeotropic alignments. To understand the mechanism of such high temperature NLC, we have performed dielectric spectroscopy in frequency range 100 Hz to 10 MHz. The different dielectric parameters, viz., effective dielectric permittivity and dielectric anisotropy of the sample have been determined with the variation of frequency and temperature. It is found that the dielectric parameters depend on dipole moment and rotation of side chain of molecule. The phase transition of this high temperature NLC has been confirmed by the DSC study.